Influence of reverse osmosis membrane age on rejection of NDMA precursors and formation of NDMA in finished water after full advanced treatment for potable reuse. (October 2019) - Roback, Shannon L.; Ishida, Kenneth P.; Plumlee, Megan H.
Abstract: The influence of reverse osmosis (RO) membrane age on rejection of N -nitrosodimethylamine (NDMA) precursors was evaluated for a full-scale potable water reuse facility. The rejection of NDMA precursors decreased slightly with increased membrane age in most RO membrane products evaluated, but remained high overall (91% average). Chloride rejection was well-correlated with rejection of NDMA precursors. Precursor removal varied (75–98%) by membrane product, with certain membrane products maintaining better precursor rejection over time. NDMA rejection, however, did not decline significantly over time, while passage of other low molecular weight organics (LMWOs) increased with membrane age. Thus, rejection of NDMA was not highly correlated with rejection of these LMWOs, suggesting that NDMA is not a good surrogate for these compounds. Incomplete removal of NDMA precursors by RO and a UV/advanced oxidation process (UV/AOP) led to NDMA formation in the finished water and miles downstream in the transmission pipelines. An average NDMA formation rate of 0.7 ng/L/hr in the transmission lines was observed, despite typical removal of NDMA by UV/AOP to non-detect levels. The study indicates that RO membranes throughout their lifetime are not an absolute barrier to NDMA precursors, and that while older membranes continue to sufficiently remove NDMA precursors to a high degree, NDMA precursor rejection may decrease slightly as membranes age. Thus, the potential exists for NDMA to form from these precursors in purified, potable reuse water after treatment despite the effective removal of NDMA by UV/AOP. Highlights: RO membrane NDMA precursor rejection decreased with increased membrane age. NDMA rejection did not appear to decrease with membrane age but was quite variable. Passage of chlorinated disinfection byproducts also increased with RO membrane age. RO membrane cleaning increased the passage of NDMA and NDMA precursors. NDMA formation continued at a rate of 0.7 ng/L/hr post treatment in delivery transmission lines.